2018
DOI: 10.1093/alcalc/agy001
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction as a Moderator of Risky Alcohol Consumers’ Attitude Towards Screening and Brief Intervention: A Cross Sectional Survey

Abstract: SBI attitude of general practice patients depends on their drinking status: abstainers or low-level consumers revealed a more positive attitude towards SBI than risky consumers. This effect is moderated by the patient's satisfaction. Risky consumers show a more positive attitude towards SBI if they are satisfied with their GP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…[58][59][60] Previous quantitative research has found that patients have more positive attitudes toward alcohol-related interventions in PCPs if they are generally satisfied with their PCP provider. 61 Qualitative research also highlights the importance of the patient-provider relationship in helping patients address their alcohol use in the PCP setting. 62 The importance of supportive providers who are comfortable providing AUD care in PCPs cannot be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60] Previous quantitative research has found that patients have more positive attitudes toward alcohol-related interventions in PCPs if they are generally satisfied with their PCP provider. 61 Qualitative research also highlights the importance of the patient-provider relationship in helping patients address their alcohol use in the PCP setting. 62 The importance of supportive providers who are comfortable providing AUD care in PCPs cannot be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Dem steht die Befürchtung entgegen, dass das Arzt-Patienten-Verhältnis darunter leiden könne, wenn Betroffene auf ihren Konsum angesprochen werden. Andersherum wird die Bedeutung eines guten Arzt-Patienten-Verhältnisses in einer aktuellen Studie für die erfolgreiche Durchführung von Kurzinterventionen in der Hausarztpraxis hervorgehoben [20]. Bei bestehender günstiger Arzt-Patienten Beziehung muss das Ansprechen des Alkoholkonsums in Form einer Kurzintervention demzufolge keine negativen Konsequenzen haben sondern kann im Gegenteil als positiver Faktor für das Gelingen der Intervention angesehen werden.…”
Section: Betroffene/angehörigeunclassified
“…Darüber hinaus können eine positive Einstellung gegenüber den entsprechenden Leitlinienempfehlungen [7], die wahrgenommenen Fähigkeiten (z. B. Gesprächsführung) [19] oder auch die Qualität der Behandler-Patient Beziehung [20] die Umsetzung von Leitlinienempfehlungen wahrscheinlicher machen oder bei Nichtvorhandensein als Barriere fungieren. In dieser Befragung wurden diese Aspekte nicht häufig als Barriere benannt, vermutlich da dies bei fehlender Kenntnis der entsprechenden Leitlinie schwer zu beurteilen ist.…”
Section: Studiendurchführungunclassified